Pengaruh Kompetensi Pedagogik Guru Terhadap Efektifitas Belajar Siswa - Stefen Deni Besare; Mardince Sasingan; Yusuf Zakarias Manutede (Universitas Cokroaminoto Palopo, 2024)
Teacher attention to student conditions during the learning process must be maximized, student seriousness when learning needs to be improved, teaching methods should be developed to be more varied and interesting, learning media must be developed to be innovative and better learning evaluations. This condition will have an impact on the effectiveness of student learning. The research was conducted at Tobelo Elementary School, grade III with the number of students taken as the research sample was 36 students. This study aims to determine the effect of teacher pedagogical competence variables on student learning effectiveness variables in class III of Tobelo Elementary School. Quantitative method with simple regression analysis technique was chosen and considered relevant to the research title. Therefore, the data analysis technique used is a simple regression test. The sampling technique used population samples, namely all third-grade students of Tobelo Multilevel Elementary School totalling 36 people. Data collection techniques using questionnaires and documentation. The questionnaire uses a Likert scale with 4 answer options for each item. Prerequisite tests were carried out with stages; description analysis, reliability validity test, data normality test, data linearity test, research hypothesis test. The results obtained by the regression equation model